Aplikasi Giberelin (Ga3) dan Perlakuan Vernalisasi Untuk Meningkatkan Produksi Benih Botani (True Shallot Seed) Bawang Merah Asal Kecamatan Miomaffo Barat - Anna Tefa; Maria Afnita Lelang (Fakultas Pertanian, Universitas Timor, 2022)
One strategy to increase the production and quality of shallots is to encourage the use of planting material through seeds known as true shallot seed (TSS). The purpose of this study is to increase the production of TSS seeds and improve the quality of TSS onion seed from Miomaffo Barat subdistrict. This research used the Randomized Block Design factorial. The first factor was an application of gibberellin (GA3), consisted of three treatments i.e without GA3 (control) applications, GA3 100 ppm applications and GA3 200 ppm applications. The second factor was vernalization treatment at 10 oC temperature with three treatments i.e without vernalization (control), vernalization for 2 weeks and vernalization for 4 weeks. The results showed that the highest number of capsule peracel was found in vernaliazation treatment 2 and 4 weeks that is 60.67 and 59.00. The highest number of sealed pest capsules was found in 2 and 4 weeks vernalization treatment, 42.75 and 54.83. The highest number of seeds was found in 4 weeks' vernalization treatment with the value is 108.14. The number of seed showed that no significantly difference on the all of treatment. The highest of a maximum growth potential was found in 4 weeks of vernalization treatment 70%, germination on 4 week vernalization treatment, 50%, vigor index on 4 week vernalization treatment, 46.00%.